STUDI DESKRIPTIF KEPATUHAN PENGOBATAN DENGAN DUKUNGAN KELUARGA, STATUS BEKERJA, DAN EFEK SAMPING PADA PASIEN KOINFEKSI TB-HIV DI SEMARANG - Annisa, Yunita; Adi, Mateus Sakundarno; Saraswati, Lintang Dian; Udijono, Ari (Fakultas Kesehatan Masyarakat, 2017)
TB-HIV co-infected patients underwent TB treatment and then continued with HIV treatment that was their burden. Saturation, side effects that will appear and other factors will affect patient compliance. Compliance of patients in the treatment is necessary for effective and successful treatment. Family support, patient working status, side effects, patient knowledge level, susceptibility, patient seriousness, perceived patient benefits and patient-acquired barriers during treatment will affect patient adherence in TB-HIV co-infected patients treatment. The aim of this study was to describe treatment adherence and related factors in TB-HIV co-infected patients. This research is descriptive research using quantitative method and cross sectional study design. The population of this study were all TB-HIV co-infected patients who were recorded and underwent treatment at the Health Care of Semarang Society, which amounted to 61 respondents. The results of this study showed that respondents with good TB-HIV co-infection adherence were better in respondents who had respondents who lacked family support (74.1%), respondents who had jobs (75.0%), and respondents who experienced the effects Side drug (80.5%). It can be concluded that respondents who have good compliance have lack of family support, have a job, and experience side effects.